2009
DOI: 10.1523/jneurosci.5176-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Inhibition during Burst Suppression Induced with Isoflurane Anesthesia

Abstract: Isoflurane is a widely used anesthetic which safely and reversibly induces deep coma and associated burst suppression (BS) electroencephalographic patterns. Here we investigate possible underlying causes for the state of cortical hyperexcitability which was recently shown to be one of the characteristics of BS. Our hypothesis was that cortical inhibition is diminished during isoflurane-induced BS. Experiments were performed in vivo using intracellular recordings of cortical neurons to assess their responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
128
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 59 publications
(67 reference statements)
13
128
0
1
Order By: Relevance
“…These maximum ⌬Q were found for Gaussian widths between 0.116 and 0.289 s (corresponding to bin sizes between 0.4 and 1 s) in each window (Fig. 6 B), consistent with the detected correlated activity following the Ͻ1 Hz slow-wave oscillations under isoflurane (Ferron et al, 2009). The number of groups giving maximum ⌬Q was predominantly two, and occasionally three or four (Fig.…”
Section: Detecting Groups In Simultaneous Multineuron Recordingssupporting
confidence: 84%
See 2 more Smart Citations
“…These maximum ⌬Q were found for Gaussian widths between 0.116 and 0.289 s (corresponding to bin sizes between 0.4 and 1 s) in each window (Fig. 6 B), consistent with the detected correlated activity following the Ͻ1 Hz slow-wave oscillations under isoflurane (Ferron et al, 2009). The number of groups giving maximum ⌬Q was predominantly two, and occasionally three or four (Fig.…”
Section: Detecting Groups In Simultaneous Multineuron Recordingssupporting
confidence: 84%
“…The less-dominated group also had occasional brief periods of simultaneous spiking, and a sustained period of spiking lasting Ͼ10 s. The population activities of the two groups' were antiphase at very low frequencies (Ͻ0.4 Hz), but in phase at the slightly higher frequencies (0.5-1 Hz) that normally comprise the peaks in cortical EEG/LFP spectra (Ferron et al, 2009). Thus, the detected groups at this timescale correspond to neurons with an anti-phase, very slow oscillation, upon which is superimposed the widely reported in-phase ϳ1 Hz slow-oscillation.…”
Section: Detecting Groups In Simultaneous Multineuron Recordingsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the low input resistance obtained in this study might reflect only the somatic domain, with possible contributions from the currents through gap junctions. Indeed, the closure of gap junctions with high concentrations of isoflurane has produced higher input resistance in a subpopulation of cat glial cells (Ferron et al, 2009).…”
Section: Absence Of K Ir 41 Channels Leads To Depolarization Of the mentioning
confidence: 99%
“…In particular, the early work of Steriade et al (10) helped establish the neural correlates of burst suppression, including the differential participation of cortical and subcortical cell types. More recent studies (11,12) have suggested that burst suppression is associated with enhanced excitability in cortical networks. These studies implicate extracellular calcium as a correlate for the switches between burst and suppression.…”
mentioning
confidence: 99%